2023
DOI: 10.1177/08853282231189779
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in vitro characterization studies of astaxanthin-loaded nanostructured lipid carriers with antioxidant properties

Abstract: The purpose of this study was to evaluate the astaxanthin-loaded nanostructured lipid carriers (ASX-NLC) prepared using a high-pressure homogenization transport system for local application of astaxanthin. Dynamic light scattering (DLS) and X-ray diffraction (XRD) were used to study the effect of microencapsulation on the properties of ASX-NLC. The mean size of ASX-NLC was about 108.43 ± 0.26 nm and PdI was 0.176 ± 0.002. The ASX-NLC had high encapsulation efficiency which was 95.69 ± 0.13%. Good light stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The data showed that the amount of drug released by the AST group was 60.1 ± 1.73% at 2 h and 70.3 ± 2.36% at 8 h. For AST@PLGA, the highest release rate was observed within 1 h, which accounted for 37.2 ± 3.82% of the total. This could be due to the loss of weakly adsorbed AST molecules on or near the surface of AST@PLGA (25). The release rate of AST@PLGA progressively slowed between 1 and 4 h; However, drug release persisted.…”
Section: The Drug Loading Of Ast@plga and In Viro Release Studymentioning
confidence: 99%
“…The data showed that the amount of drug released by the AST group was 60.1 ± 1.73% at 2 h and 70.3 ± 2.36% at 8 h. For AST@PLGA, the highest release rate was observed within 1 h, which accounted for 37.2 ± 3.82% of the total. This could be due to the loss of weakly adsorbed AST molecules on or near the surface of AST@PLGA (25). The release rate of AST@PLGA progressively slowed between 1 and 4 h; However, drug release persisted.…”
Section: The Drug Loading Of Ast@plga and In Viro Release Studymentioning
confidence: 99%
“…The ketocarotenoid astaxanthin (3,3 ′ -dihydroxyβ, β'-carotene-4,4 ′ -dione) is a red pigment with antioxidant activity as a result of its hydroxyl and keto groups [2]. Astaxanthin is used as a raw material for pharmaceuticals and functional foods because it suppresses inflammation, is nontoxic, and prevents diabetes and cancer [2,3]. By 2027, the market value of astaxanthin is expected to increase to USD 3.4 billion [4].…”
Section: Introductionmentioning
confidence: 99%